Transforming Ethiopia’s agroadvisory: Harmonizing two agronomy use-cases for tailored, site-specific agronomic solutions - Desta, Lulseged Tamene; Mesfin, Tewodros; Degefie, Tibebe; Chernet, Meklit; Abera, Wuletawu; Tilaye, Asmalu; Ebrahim, Mohammed; Yitaferu, Birru; Abera, Dejene (2025)
The Alliance- and ICRISAT-led Excellence in Agronomy (EiA) Initiative use cases are transforming Ethiopia's agroadvisory services with tailored, site-specific agronomic solutions. By harmonizing the Alliance’s NextGen agroadvisory and ICRISAT’s landscape-based Decision Support Tools (DSTs) into a unified platform, the Initiative is enhancing advisory precision, reducing duplication, and minimizing stakeholder confusion. The National Agricultural Research System validated the harmonized DST on 2,500 crop farms, confirming its effectiveness. The Ministry of Agriculture aims to scale this technology to reach 4 million farmers by 2030, driving sustainable agricultural transformation nationwide.